Use of ICT in Teaching Conic Section - Poudel, Gajendra (The Journal of Aadikavi, 2023)
This study entitled “Use of ICT in conic section: An experimental study” is an experimental research. ICT can be applied in conic sections which include parabola, ellipse, hyperbola, circle etc. For graphics and visualisation, geometric modelling, optics and imaging, satellite orbits, signal processing, engineering design, architectural design; ICT is used. The objectives of the study was “to compare the achievement of students taught by using ICT software and conventional teaching method while teaching conic section of grade XII.” The research was based on Vigotski’s constructivist view of learning. A pre-test and post-test of quasi-experimental research design was used to find the students’ achievement after experiment. Conventional sampling were used and two sections of Aadikavi bhanubhakta Secondary School were selected. Two sections were observed as Section ‘A’ of class XII was used for conventional group and section ‘B’ was used for experimental group. The school is located in Vyas Municipality ward no.1. There 28 students in section ‘A’ and 28 students in section ‘B’. For data collection, researcher used MAT. The result of Mathematics Achievement Test indicated that there was a significant difference between the average achievement of students taught by using ICT software and without using ICT software on post-test. The finding illustrated that the students in the experimental group performed better when using ICT software like Geogebra and Mathematica than the control group with the conventional method.